Patient-reported outcome measures in patients with familial cerebral cavernous malformations: results from the Treat_CCM trial - Meessen, Jennifer M. T. A.; Abete-Fornara, Giorgia; Zarino, Barbara; Castori, Marco; Tassi, Laura; Carriero, Maria R.; D'Alessandris, Q. G.; Al-Shahi Salman, R.; Blanda, Adriana; Nicolis, Enrico B.; Novelli, Deborah; Caruana, Maria; et al. (Frontiers in Neurology, 2024)
The Phase 1/2 Treat_CCM randomized controlled trial for people with familial cerebral cavernous malformations (FCCM) confirmed the safety of propranolol and suggested beneficial effects on intracerebral hemorrhage or new focal neurological deficit, but the effects on patient reported outcome measures have not been reported.Methods: Participants completed self-reported questionnaires at baseline, 1 and 2 years. Depression was assessed with the Beck Depression Inventory-II (BDI-2); Anxiety with the Stait-Trait Anxiety Inventory X1 & X2 (STAI X-1 & STAI X-2) and Quality of Life with the Short Form 36 (SF-36), split into the physical and mental component scale (PCS and MCS). Differences between treatment groups and general population were assessed. Change over time by treatment was assessed by means of mixed models.Results: Seventy-one participants (48 propranolol, 23 standard care) were enrolled, of whom 61(73%) completed questionnaires at baseline and 2 year FU. At baseline, no differences between treatment groups for any of the questionnaires were present. Twenty (31.7%) patients were considered depressed at baseline, while this proportion was lower in the propranolol group after 2 years (28.6% vs 55.5%, p=0.047). The STAI X-1 and X-2 scores were stable over time. PCS was lower in FCCM patients as compared with the general Italian population, while the MCS was similar to the general population. No effect of propranolol was found for both PCS and MCS.Depression is common amongst patients with FCCM. Patients randomized to propranolol had a lower proportion of participants with depression after 2 years.The Treat_CCM trial is registered at EudraCT (2017-003595-30) and ClinicalTrials.gov (NCT03589014) and has been closed by December 2021.